Understanding social constructs of the Kandyan period: An examination of apparel accessories depicted in temple murals belonging to the Kandyan period: A study conducted on selected temples of the Kandyan period - Premaratne, L. D. M.; Nishanthi, M.; Neththasinghe, N. M. (Department of Anthropology, USJ, 2022)
The advent of Sangamittha, along with the Sri Mahabodhi sapling and a delegation drawn from 18 castes, including those of the painter/artist caste contributed to the propagation of the fresco and mural tradition, which had begun way back in the third century in the island, in numerous ways. This art, which was developed along traditional lines prospered during the Kandyan Period. Despite the permission granted for the adorning of a deep orange colour (Guru in the vernacular) or white, the Vinaya Pitka’s section ‘Chullavagga Paliya’ prohibits the depiction of the human form. Literature: including legends, and chronicles related to King Dutugemunu, Parakramabahu I, and the Visuddhimagga has taken note of the mural and fresco culture of the island. The kingdom underwent a series of chaos from its establishment as a kingdom in the early 17th Century to the coronation of its last king – Keerthi Sri Weera Parakrama Narendrasinghe in the 18th Century. Literature suggests that Keerthi Sri Rajasinghe rises to the throne in 1747 AD and that he seeks the consultation of Ven Welivita Saranankara. The literature also suggests that the king embraced the teachings of Lord Buddha under the tutelage, guidance and influence of the Ven. Welivita Saranankara Sangharaja, and further led an attempt to reform Buddhism in the island, which resulted in a Renaissance of Buddhism. The king also undertook the renovation of Buddhist viharas previously destroyed by invaders, while building several new viharas. During this period, art in temples took a novel form, with specific characteristics, including the use of symbology, developing an independent tradition of art, differentiating itself from the classical tradition. This paper attempts to answer the question, “Was the artist able to demonstrate the class structure that existed in the society of the time?”, with the objective of examining and unraveling through the apparel accessories depicted in the temple frescoes/murals, to understand elements of the society during that period. This study employed primary and secondary data to explore the frescoes and murals in temples belonging to the Kandyan period in detail. This study concludes that the artist of the Kandyan period, using symbology and apparel accessories in the Temple art of the period, has managed to portray the Kandyan society of the period and its social constructs successfully. This study reveals that the exemplary artist/painter of the Kandyan period has, in fact, employed apparel accessories of the period, including jewelry, on the characters in frescoes/ murals that form temple art. The schematic use of these characters in the art that the artist has not personally seen, is a testimony to his/her effort.
Keywords: Artists, Attires, Contemporary Society, Kandyan Paintings, Temple